FinTech and Financial Capability, What Do We Know and What We Do Not Know : A Scoping Review - Joseph, David; S., Girish; G., Suresh (Indian Journal of Finance, 2023)
Purpose : The scoping review of this study was to investigate the existing literature on FinTech's impact on financial competence and draw conclusions from it. We applied Danielle Levac's recommendations and used the scoping review framework developed by Arksey and O'Malley. Design/Methodology/Approach : The study involved identifying and analyzing 246 papers from major databases, followed by a rigorous screening process to select 54 relevant studies. Data coding, inclusion, and exclusion screening were conducted by us independently. Findings : According to the findings, studies on FinTech and financial capacity started in 2012, and since 2020, the number of studies has sharply increased. The analysis showed that financial inclusion was the primary focus of the major FinTech studies, suggesting possible research gaps in other aspects of financial competence. We suggested recommendations and prospective directions for further research in this developing subject based on these findings. Managerial Implications : This knowledge will help managers find opportunities for collaboration, offer fresh perspectives, and make wise choices, which will improve the sector. Theoretical Implications : Important concepts and relationships were found, new trends were highlighted, and theoretical advancements were suggested as a result of the inquiry. Through the filling of knowledge gaps, the study would guide future theoretical development, facilitate diverse perspectives, and support the construction of robust frameworks in the FinTech and financial capabilities sector. Originality/Value : This study offered a comprehensive review of the body of literature, pointing out areas in need of more research and knowledge gaps. The review's unique perspective for future study and innovation in understanding the relationship between FinTech and financial capacity is derived from its thorough synthesis of many studies.